2014
DOI: 10.1108/prog-02-2012-0005
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Web 2.0 adoption: a case study

Abstract: Purpose – The main purpose of this paper is to identify factors affecting the adoption of Web 2.0 tools by librarians of academic libraries located in Hamedan, Iran. Design/methodology/approach – Methodologically, this survey is applied using a descriptive approach. The statistical population of the survey was 47 librarians of academic and college libraries located in Hamedan (Iran). The tool used for data gathering is a questionnaire ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…In a factor approach study, Alireza and Mansoureh (2014) discussed that, the effective factors playing key role to adopt web 2.0 applications in academic libraries are job conditions, changeability, skills, competitiveness and saving time. Baro et al (2014) investigated the awareness and use of web 2.0 among librarians in the university libraries in Africa and found that Facebook, blog, Twitter, IMs and Wikis were the most used for reference services for announcing library news/events, photo and video sharing and training programmes to users.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…In a factor approach study, Alireza and Mansoureh (2014) discussed that, the effective factors playing key role to adopt web 2.0 applications in academic libraries are job conditions, changeability, skills, competitiveness and saving time. Baro et al (2014) investigated the awareness and use of web 2.0 among librarians in the university libraries in Africa and found that Facebook, blog, Twitter, IMs and Wikis were the most used for reference services for announcing library news/events, photo and video sharing and training programmes to users.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…Podemos decir que hoy día el uso de los medios sociales ha alcanzado su punto de madurez debido al uso generalizado, aunque no sin reticencias y críticas (Parry, 2012; Cefrio, 2012; Ravindran, Chua, Kuan, Goh y Lian, 2014;Isfandyari-Moghaddam y Hosseini-Shoar, 2014). Los dispositivos móviles tienen una importancia estratégica en el auge de los medios sociales y las tecnologías ponibles o el internet de las cosas, están potenciando aún más su aspecto social.…”
Section: La Web Social Las Organizaciones Y Las Bibliotecasunclassified
“…In information era Web 2.0 are a tool that has been widely used by library associations in order to disseminate a variety of information to the wider users. The use of Web 2.0 in different universities (Ahmad et al, 2013;Chaurasia, 2011;Ram et al, 2011) in medical-related organizations (Chu et al, 2011), civil society organizations (Shi, 2013) and several libraries including national libraries (Isfandyari-Moghaddam and Hosseini-Shoar, 2014;Arif and Mahmood, 2012;Buigues-Garcia and Gimenez-Chornet, 2012;Naqvi, 2012;Han and Liu, 2010;Kim and Abbas, 2010). The use of Web 2.0 in different library associations (Satpathi et al, 2012;Mahmood and Richardson, 2011;Chua and Goh, 2010).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Yet, building this research based on aforementioned studies, researcher try to identify and analyse factors affecting the application of Web 2.0 tools by library associations. Hopefully, the identification of such factors can lead to realizing increased as well as qualified utilization of Web 2.0 tools in library associations (Isfandyari-Moghaddam and Hosseini-Shoar, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%